(untitled) - Poliakova, Bibiana (Doprava a spoje, 2007)
The tariff integration in integrated transport systems means that the passengers travel throughout the entire network with only one ticket and pay according to the same tariff system, irrespective of how many transport companies' services they use. The choice of tariff and tariff arrangement is the key step in tariff system preparation.